Plasma Lipid Levels in Relation to Disease Severity in Sickle Cell Anaemia in Abakaliki, Southeast Nigeria - Nnachi OC; Edenya OO; Okoye HC; Akpa CO; Nwani FO; Nwani EI (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Background: Dyslipidaemia has been implicated in the pathophysiology of sickle cell disease (SCD) complications; hence its role requires further elucidation. Objectives: To investigate the relationship between disease severity and plasma lipid levels of patients with sickle cell anaemia. Methods: A cross-sectional study design was used for the survey. A total of 50 patients with sickle cell anaemia and 50 controls without SCD were recruited for the study. The clinical data and plasma lipid levels of lipids and haemoglobin parameters were analysed. Results: The majority of the participants were aged 18-25 years. Total plasma cholesterol and HDL-C were significantly lower in individuals with SCA compared with the controls (3.3±1.2 vs 4.2±1.2; p<0.001) and (1.3±0.5 vs 1.5±0.4; p = 0.038) respectively. Most patients with SCA had moderate disease severity (24; 48%). There was no statistically significant difference in the plasma levels of total cholesterol and HDL-C across the disease severity groups of SCA (p = 0.694 and 0.262). There was also no significant correlation between total cholesterol, HDL-C, and markers of haemolysis, haemoglobin F, and haemoglobin S levels. Conclusion: SCA is characterised by lower mean plasma TC and HDL than controls. However, no relationship was found between TC, HDL levels and SCD disease severity, markers of haemolysis, HbF and HbS levels. Further studies are required to ascertain the implications of plasma lipid levels in SCD.